Increase in resistance to extended-spectrum cephalosporins in Salmonella isolated from retail chicken products in Japan. - Tamie Noda (PLoS ONE, 2015)
Extended-spectrum β-lactamase (ESBL)-producing Salmonella are one of the most important public health problems in developed countries. ESBL-producing Salmonella strains have been isolated from humans in Asian countries neighboring Japan, along with strains harboring the plasmid-mediated extended-spectrum cephalosporin (ESC)-resistance gene, ampC (pAmpC). However, only a few studies have investigated the prevalence of ESC-resistant Salmonella in chicken products in Japan, which are the main vehicle of Salmonella transmission. The aim of this study was to investigate the prevalence of ESBL-producing, pAmpC-harboring, or carbapenem-resistant Salmonella in chicken products in Japan. In total, 355 out of 779 (45.6%) chicken product samples collected from 1996-2010 contained Salmonella, resulting in 378 distinct isolates. Of these isolates, 373 were tested for resistance to ESCs, cephamycins, or carbapenems. Isolates that showed resistance to one or more of these antimicrobials were then examined by PCR and DNA sequence analysis for the presence of the bla(CMY), bla(CTX-M), bla(TEM), and bla(SHV) resistance genes. Thirty-five resistant isolates were detected, including 26 isolates that contained pAmpC (bla(CMY-2)), and nine ESBL-producing isolates harboring bla(CTX-M) (n = 4, consisting of two bla(CTX-M-2) and two bla(CTX-M-15 genes)), bla(TEM) (n = 4, consisting of one bla(TEM-20) and three bla(TEM-52) genes), and bla(SHV) (n = 1, bla(SHV-12)). All pAmpC-harboring and ESBL-producing Salmonella isolates were obtained from samples collected after 2005, and the percentage of resistant isolates increased significantly from 0% in 2004 to 27.9% in 2010 (P for trend = 0.006). This increase was caused in part by an increase in the number of Salmonella enterica subsp. enterica serovar Infantis strains harboring an approximately 280-kb plasmid containing bla(CMY-2) in proximity to ISEcp1. The dissemination of ESC-resistant Salmonella containing plasmid-mediated bla(CMY-2) in chicken products indicates the need for the development of continuous monitoring strategies in the interests of public health.